SIGNIFICANCE OF ANATOMICAL STRUCTURE AND PHYSIOLOGICAL FUNCTIONS IN LEARNING SWIMMING TECHNIQUES (American Journal of Research in Humanities and Social Sciences, 2023)
In the process of learning swimming techniques, the importance of the athlete's anatomical structure and physiological functions has been explained.